Pembuatan alat pemurni air laut skala besar untuk memenuhi kebutuhan air bersih di SMA Negeri 1 Rupat daerah pesisir Provinsi Riau - Ernidawati Ernidawati; Azizahwati Azizahwati; Defni Satria; Annisa Jannata Firdausi; Maria Desfina Sitorus; Aldi Syahrul Khunaivi; Anisa Siti Nurhasanah; Elvira Elvira; Raihan Syadza Suratman; Yuniati Efalingga; Yupika Yupika; Sry Khayrani br. Sinaga; Widari Cania (Riau Journal of Empowerment, 2022)
Rupat Island located at a coastal area of Riau Province, generally coastal areas are identical with the availability of clean water. The low availability of clean water has a negative impact on all sectors. The water used by students and teachers at SMA Negeri 1 Rupat comes from a ring well which tastes salty and brackish. Problems in the health sector are the availability of clean water that is suitable for consumption, education is insufficient equipment for Physics Experiments, in the economic field, family spending increases due to the availability of bottled water, and the field of community empowerment has not maximized the use of natural resources. The solution for this aspect is technological innovation that is able to meet the need for clean water in the long term by utilizing existing potential, one of which is the manufacture of a sea water purifier, a giant measuring 4x4 meter. The tool's fundamental working principle is to evaporate the air first and then collect the condensed water to separate the mineral salts and contaminants from the seawater. The author has made a seawater purifier measuring 48x38 cm as a medium for high school physics learning in 2021 with a TKT 5.